Beyond the species pool: modification of species dispersal, establishment, and assembly by habitat restoration - Török, Péter; Helm, Aveliina; Kiehl, Kathrin; Buisson, Elise; Valkó, Orsolya (Restoration ecology, 2018)
Species dispersal, establishment, and assembly are crucial stages of the life history of plants, and clear understanding of the governing forces and rules that shape species composition in a particular community is vital for successful ecological restoration. In this article, we focus on five aspects of seed dispersal and plant establishment, which should be considered during habitat restoration actions. In the first two sections, we discuss the success of spontaneous dispersal and establishment on restoration based on either spatial dispersal or local seed banks. In the third section, we assess the possibilities of species introduction and assisted dispersal. In the fourth section, we introduce some possibilities for the improvement of establishment success of spontaneously dispersed or introduced species. Finally, we highlight issues influencing long‐term persistence and sustainability of restored habitats, related to the alteration of management type and intensity, climate change, and spread of non‐native species. With the present article, we introduce the special issue entitled “Seed dispersal and soil seed banks – promising sources for ecological restoration” containing 15 papers by 62 authors from 10 countries arranged in the abovementioned five topics.